Revitalizing the Elementary School’s Management of Curriculum and Learning During the Pandemic Era - Bunga Bhagasasih Al-Kansa; Mila Lisnadiani Iswanda; Husen Windayana (Indonesian Journal of Multidisciplinary Science, 2021)
Curriculum management is a form of joint effort in order to streamline the achievement of goals in terms of teaching, especially in improving the quality of teaching and learning. In its implementation, there is a need for planning, implementation, and evaluation, all three of which are an integral series. In the current pandemic, curriculum management becomes the main urgency in education in Indonesia, because, without curriculum management, learning becomes not maximal and inhibits various activities of human life. Using qualitative research through literature studies, we try to examine how curriculum management and learning implementation in schools during the current pandemic and examine what effective ways can be done during learning in the Covid-19 pandemic.